2012
DOI: 10.4103/0250-474x.106061
|View full text |Cite
|
Sign up to set email alerts
|

Stability-indicating reversed-phase liquid chromatographic method for simultaneous determination of losartan potassium and ramipril in tablets

Abstract: A stability-indicating reversed-phase liquid chromatographic method has been developed and validated for simultaneous determination of losartan potassium and ramipril. Separations were achieved using a C18 column with mobile phase consisting of acetonitrile and (0.2% v/v, pH 2.5) aqueous trifluoroacetic acid (45:55, v/v) in isocratic mode at 1 ml/min flow rate. Column effluent was monitored at 210 nm using a UV detector. The method was validated for selectivity, linearity, accuracy, precision, sensitivity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…As shown in Figure 5, photolysis can be considered negligible since LOS removal did not exceed 5% under solar irradiation alone. This finding agrees with Kollipara et al, who highlighted the notable stability of LOS under photolytic stress conditions [35]. Additionally, a control experiment conducted in the dark for 30 min revealed that LOS removal due to adsorption phenomena was less than 20%, in line with previous results [16].…”
Section: Effect Of Operating Parameters On Los Degradationsupporting
confidence: 92%
“…As shown in Figure 5, photolysis can be considered negligible since LOS removal did not exceed 5% under solar irradiation alone. This finding agrees with Kollipara et al, who highlighted the notable stability of LOS under photolytic stress conditions [35]. Additionally, a control experiment conducted in the dark for 30 min revealed that LOS removal due to adsorption phenomena was less than 20%, in line with previous results [16].…”
Section: Effect Of Operating Parameters On Los Degradationsupporting
confidence: 92%